Débat étatsunien sur les statistiques ethno-raciales : l’exemple de la Proposition 54 en Californie - Olivier Richomme (Transatlantica)
In the U.S., public debates about the legitimacy of the classification of the American population along ethno-racial lines are quite rare. However, in 2003, voters in California had the opportunity to express their views on the necessity of this form of classification via referendum. This campaign was in many ways atypical but it still illustrates the complex and controversial nature of the debate about ethno-racial classification and the public policies relying on it. Moreover, it shows how difficult it is to launch a real political debate about ethno-racial taxonomy. This question is tangled in deep partisan divisions and, even when the opportunity presents itself, the American society seems unwilling to start any serious discussion about the very nature of the identities and the political representations created by ethno-racial statistics.